Mechanism of Cu entry into the brain: many unanswered questions - Shubhrajit Roy; Svetlana Lutsenko (Neural Regeneration Research, 2024)
Brain tissue requires high amounts of copper (Cu) for its key physiological processes, such as energy production, neurotransmitter synthesis, maturation of neuropeptides, myelination, synaptic plasticity, and radical scavenging. The requirements for Cu in the brain vary depending on specific brain regions, cell types, organism age, and nutritional status. Cu imbalances cause or contribute to several life-threatening neurologic disorders including Menkes disease, Wilson disease, Alzheimer’s disease, Parkinson’s disease, and others. Despite the well-established role of Cu homeostasis in brain development and function, the mechanisms that govern Cu delivery to the brain are not well defined. This review summarizes available information on Cu transfer through the brain barriers and discusses issues that require further research.